Intrinsic nutrients and defensive compounds drive coarse woody debris decay in five dominant subtropical tree species, China - Xiaoyu Wang; Tingsi Xie; Hui Chen; Shangbin Bai; Nan Wang (iScience)
Summary: Coarse woody debris (CWD) is crucial for carbon and nutrient cycling in forest ecosystems, with decomposition rates influenced by species-specific wood traits. This five-year study in a subtropical Chinese forest evaluated the CWD decomposition of five dominant species. Results showed that broadleaved species decomposed fastest (k = 0.230 years−1), followed by moso bamboo (0.168 years−1), and conifers slowest (0.022 years−1). Fast-decaying species were characterized by high hemicellulose, cellulose, and phosphorus (P) content, with rapid P release within the first decay year and nitrogen (N) accumulation over time. Tannin initially inhibited decay in fast-decaying species, but defensive compounds (tannins and phenolics) showed no sustained effect on decomposition rates. These findings indicate active CWD decomposition in subtropical forests, where P limitation outweighs N for broadleaves and bamboo. Defensive compounds only weakly influenced early-stage decay. Our results enhance the understanding of deadwood decomposition and carbon sink dynamics in subtropical ecosystems.